Electrolyte Abnormalities in Hospitalized COVID- 19 Patients: An Observational Study (Chest & Heart Journal, 2023)
Background: Coronavirus disease 2019 (COVID-19) is a potentially fatal disease with multisystem involvement. Electrolyte abnormalities are not uncommon in coronavirus disease 2019 (COVID-19). Several studies have suggested that various electrolyte imbalances seem to have an impact on disease prognosis.Objective: The primary objective of the present study was to evaluate the pattern of electrolyte abnormalities in hospitalized COVID-19 patients.Methods: This retrospective study was conducted in the Department of Respiratory Medicine, National Institute of Diseases of the Chest & Hospital, Mohakhali, Dhaka, between January 2021 and June 2021. A total of 51 patients with COVID-19 were included in the study. Baseline levels of sodium, potassium, calcium and chloride were assessed and the effects of abnormalities in these electrolytes were evaluated. Patients demographic profile, clinical features, admission electrolyte report were documented in case record forms. Collected data were compiled and appropriate analyses were done by using computer based software. Chi-squre test was used to analyse the categorical variaties. A p-value